Corrupting learning: Evidence from missing federal education funds in Brazil - Claudio Ferraz; Frederico S. Finan; Diana B. Moreira (Institute for the Study of Labor (IZA), 2012)
This paper examines if money matters in education by looking at whether missing resources due to corruption affect student outcomes. We use data from the auditing of Brazil's local governments to construct objective measures of corruption involving educational block grants transferred from the central government to municipalities. Using variation in the incidence of corruption across municipalities and controlling for student, school, and municipal characteristics, we find a significant negative association between corruption and the school performance of primary school students. Students residing in municipalities where corruption in education was detected score 0.35 standard deviations less on standardized tests, and have significantly higher dropout and failure rates. Using a rich dataset of school infrastructure and teacher and principal questionnaires, we also find that school inputs such as computer labs, teaching supplies, and teacher training are reduced in the presence of corruption. Overall, our findings suggest that in environments where basic schooling resources are lacking, money does matter for student achievement.
Keywords: D73; I21; H72; 330; corruption; test scores; local governments; Brazil; Korruption; Bildungsniveau; Kommunalverwaltung; Öffentliche Bildungsausgaben; Finanzausgleich; Brasilien